2015
DOI: 10.22146/agritech.9417
|View full text |Cite
|
Sign up to set email alerts
|

KOMPOSISI KIMIA SERTA AKTIVITAS ANTIOKSIDAN EKSTRAK HIDROFILIK BEKATUL BEBERAPA VARIETAS PADI (Chemical Composition and Antioxidant Activity of Rice Bran Hydrophilic Extract of Selected Rice Variety)

Abstract: The study was aimed to investigate chemical composition, dietary fiber content and the antioxidant activity of the hydrophilic extract of varieties of rice bran IR-64, Sintanur, Rajalele and Menthikwangi. Rice bran from each sample was analyzed proximate and fiber content. Hydrophilic extract was obtained by extracting each sample of bran with methanol solvent. Total phenolic content was tested by Folin Ciocalteu reagent and antioxidant activity of the extract was tested by DPPH (2,2-diphenyl-1-picrylhydrazyl) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Saenkod et al (2013) also proved different varieties of brown rice from China had different antioxidant activity and total phenolic compound. Hartati et al (2015) also reported that a variety of rice influencing the antioxidant activity and phytochemical content and between IR-64, Sintanur, Rajalele, and Menthik. Menthik was observed as the best for total phenolic content and antioxidant activity.…”
Section: Determination Of Antioxidant Properties and Phytochemical Comentioning
confidence: 91%
See 1 more Smart Citation
“…Saenkod et al (2013) also proved different varieties of brown rice from China had different antioxidant activity and total phenolic compound. Hartati et al (2015) also reported that a variety of rice influencing the antioxidant activity and phytochemical content and between IR-64, Sintanur, Rajalele, and Menthik. Menthik was observed as the best for total phenolic content and antioxidant activity.…”
Section: Determination Of Antioxidant Properties and Phytochemical Comentioning
confidence: 91%
“…Menthik was observed as the best for total phenolic content and antioxidant activity. Furthermore, Huang and Ng (2012) and Hartati et al (2015) also showed that higher total phenolic content of rice bran also give a higher antioxidant activity.…”
Section: Determination Of Antioxidant Properties and Phytochemical Comentioning
confidence: 91%
“…Selulosa menyediakan bahan pengenyang dan bahan kasar pada pangan yang membantu memelihara daya gerak dan kesehatan saluran pencernaan (Khoury et al, 2018 (Firman et al, 2016). Rice bran juga sebenarnya memiliki aktivitas antioksidan tinggi (Hartati et al, 2015;Arab et al, 2011), akan tetapi pada penelitian ini peningkatan jumlah SRB tidak terlihat pada peningkatan aktivitas antioksidan.…”
Section: Hasil Dan Pembahasan Analisis Total Proteinunclassified
“…Kadar abu ini lebih rendah daripada kadar abu flake pati garut oleh Amalia dan Klara (2013) yaitu sebesar 5,9%. Rice bran merupakan sumber mineral, yaitu 8,3% (Hartati et al, 2015), akan tetapi penambahannya tidak mengakibatkan kadar mineral BMF ini menjadi tinggi.…”
Section: Verifikasi Formula Optimumunclassified
“…Many studies have revealed that bran contains high bioactive components [7]; [14]; [18]. Hartati et al [10] and Hartati et al [11] extracted rice bran from several rice varieties and found that the total phenol of rice bran ranged from 2280.00 ± 60.61 to 2794.28 ± 181.83 μg Gallic Acid Equivalent (EAG)/g rice bran. Meanwhile, the highest antioxidant activity for scavenging free radicals (DPPH) was 41.28 ± 0.60%.…”
Section: Introductionmentioning
confidence: 99%